Functional independence in elderly residents in long-term institutions - Carneiro, Flávia Ravany; Brasileiro, Ismênia de Carvalho; Vasconcelos, Thiago Brasileiro de; Arruda, Vanessa da Ponte; Florêncio, Raquel Sampaio; Moreira, Thereza Maria Magalhães (Acta Fisiátrica, 2012)
Objective: To evaluate the Functional Independence Measure (FIM) for elderly women in a longterm institution in Fortaleza - CE. Method: This is an exploratory, descriptive study with a quantitative approach, performed with 59 elderly residents in two long-term institutions for the elderly (LTCF) in Fortaleza - CE, during the second half of 2010. The initial assessment instrument consisted of personal, socio-demographic, and clinical data. We then applied the Functional Independence Measure (FIM) to measure how much care they needed to perform motor and cognitive tasks. Results: The women had been institutionalized for 8.32 (± 9.46) years. The average age of participants was 76.72 (± 9.81) years. In relation to self-care most of the group eat, carry out personal hygiene, and bathe independently. In addition, it can be seen that 69.50% use the toilet independently. As for mobility, 50.85% of the women can manage without help, while 62.71% can only use the stairs with help. As for social cognition, they have good communication, because 49.15% did not need any help in understanding the words, 62.71% express themselves freely, while 50.85% have memory deficits. Conclusion: The participants in the study were independent under the general definition. They were able to perform virtually all activities in a satisfactory manner, such as feeding, personal hygiene, bathing, mobility, and sphincter control, being dependent on aid only with aspects related to memory and climbing stairs.